The Influence of Career Development, Organizational Climate, And Motivation on Employee Performance at Sidenreng Rappang Regency Water Resources Management Office - Haeranah Alwany; Maryadi Maryadi; Irfan Setiawan; Herni Herni (TRANSFORMASI: Jurnal Manajemen Pemerintahan, 2024)
The research aimed to examine the effect of career development, organizational climate, and work motivation on employee performance at the Sidenreng Rappang Regency Water Resources Management Office. The process was through the application of a quantitative method by collecting data from two important sources. The primary data were collected by distributing questionnaires to 52 respondents while secondary sources included official documents from related agencies. The data collected were analyzed using statistical methods to identify the relationship between the variables. The analysis was initiated through a Validity and Reliability test followed by Multiple Linear Regression, Hypothesis Test, and Partial t-test to evaluate the hypothesis proposed. The results showed that career development, a positive organizational climate, and high work motivation significantly influenced employee performance. This showed that the sustainable and structured combination of the three factors could increase collective employee performance and assist in achieving organizational goals.